Global well-posedness of the non-isentropic full compressible magnetohydrodynamic equations - Xu, F.; Zhang, Xinguang; Wu, Yong Hong; Caccetta, Louis (Springer, 2016)
In this paper, we are concerned with Cauchy problem for the multi-dimensional (N = 3) non-isentropic full compressible magnetohydrodynamic equations. We prove the existence and uniqueness of a global strong solution to the system for the initial data close to a stable equilibrium state in critical Besov spaces. Our method is mainly based on the uniform estimates in Besov spaces for the proper linearized system with convective terms.